(untitled) (International Seven Journal of Multidisciplinary, 2024)
The main objective of this study is to understand and reflect on the difficulties faced by two teachers in a municipal elementary school in the rural area of the municipality of Bagre-Pará, regarding the planning of pedagogical activities during the Coronavirus pandemic period - 2020/2021. The specific objectives were: to identify the challenges and uncover the difficulties faced by teachers based on the question: what are the main challenges faced by teachers when planning teaching activities during the Coronavirus pandemic? The research has a qualitative approach, using semi-structured interviews as a data collection technique. The type of research carried out was field and bibliographic research. The study was based on authors such as Barreto & Rocha (2020), Castanheira, Maciel and Martins (2008), Eliezer, Ribeiro and Schutz (2020), Libâneo (1994), Menegolla & Sant’anna (2001), Molina (2007), Gil (2008), among others. Based on the analysis of the data, it was understood that the pandemic has brought several difficulties regarding the organization of teaching work. Of particular note were the lack of adequate planning, both by the relevant municipal bodies and by the school, and the scarcity of resources to guarantee the teaching model adopted during the pandemic period - remote, in addition to the lack of knowledge of how to do it, on the part of both teachers and students, there were not the necessary conditions for this "new" teaching model. Given the facts, it can be inferred that planning is a priority element in educational institutions - whether in differentiated or regulatory periods, in order to avoid greater impacts on students’ learning, especially those who are in places without resources to facilitate their learning and thus not violate one of their fundamental rights, which is school education.